The Autophagy Regulator p62 Controls PTEN-Dependent Ciliogenesis - Mun, Hyowon; Lee, Eun Ji; Park, Minah; Oh, Goo Taeg; Park, Jong Hoon (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is a catabolic process required for maintaining intracellular energy homeostasis. It eliminates harmful proteins and recycles functional macromolecules back into the cell via cargo breakdown. Autophagy is generally suppressed under fed conditions and induced by serum starvation; therefore, it is considered to be a nutrient-sensing mechanism. Cilia, finger-like organelles harboring multiple receptors along their surface, are energy-sensing structures that are also triggered by serum deprivation. Potential interplay between these two nutrient-sensing machineries has increasingly been suggested in recent years; however, functional correlations remain controversial. Herein, we verified the effect of autophagy alterations on cilia assembly and the specific underlying mechanisms. Autophagy flux altered either by drugs or autophagy-targeting siRNAs strongly inhibited ciliogenesis and was mediated by p62, an autophagy regulator, via Pten/Dvl2/AurKA signaling. These data suggest that autophagy regulatory mechanisms may affect ciliogenesis.